Can heat conditions affect the heart rate responses, perception of effort, and technical performance of young male football players during small-sided games? a comparative study - ZhiHui Kang; Zhongju Chen; GuiYang Liu (BMC, 2024)
Abstract Background Soccer coaches often employ small-sided games (SSGs) to elicit both physiological and technical responses from players. However, numerous contextual factors can influence the outcomes of these games. This comparative study aimed to investigate how environmental temperature (< 21ºC and > 29ºC) impacts heart rate responses, perception of effort, and technical performance in young male football players during SSGs. Methods This study compares temperatures below 21ºC (∼ 20.4 ± 0.4ºC) with temperatures above 29ºC (∼ 29.7 ± 0.6ºC). This repeated measures study design involved 60 male football players at a trained/developmental level, selected from under-16 and under-19 teams. It aimed to assess the effects of the 3v3 format, conducted repeatedly under conditions of 21ºC and above 29ºC. Throughout the games, mean heart rate responses (HRmean), measured via heart rate sensors; rate of perceived exertion (RPE), assessed using the CR-10 Borg scale; and successful passes and lost balls, tracked through an ad hoc observational analysis tool, were monitored. Results No significant interactions were observed (time*age group) in meanHR (F = 0.159; p = 0.691; $$\:{η\:}_{p}^{2}$$ =0.003), RPE (F=0.646; p=0.425; $$\:{η\:}_{p}^{2}$$ =0.011), number of passes completed (F=0.204; p=0.654; $$\:{η\:}_{p}^{2}$$ =0.003), and number of lost balls (F = 0.157; p = 0.694; $$\:{η\:}_{p}^{2}$$ =0.003). Overall, significantly higher heart rate responses in mean HR (p<0.001) and RPE (p<0.001) were observed at temperatures above 29ºC, while significantly more passes were completed at temperatures below 21ºC (p<0.001). Conclusions Heat conditions significantly intensified the psychophysiological responses in players, concurrently leading to a significant impairment in the number of passes. Coaches should contemplate implementing mitigation strategies to avert performance declines during heat conditions when utilizing SSGs.